Higher patient assessed quality of chronic care is associated with lower diabetes distress among adults with early-onset type 2 diabetes: Cross-sectional survey results from the Danish DD2-study. Issue 5 (October 2020) - Bo, Anne; Jensen, Nanna Husted; Bro, Flemming; Nicolaisen, Sia Kromann; Maindal, Helle Terkildsen
Highlights: Adults with early-onset type 2 diabetes report insufficient quality of chronic care. Women and unemployed reported particularly low quality of care levels. Quality of care was reported higher among hospital than general practice patients. Diabetes distress was highest in those reporting low quality of chronic care. Early-onset individuals need targeted and multidisciplinary health care support. Abstract: Aim: Among adults aged 20–45 years with type 2 diabetes mellitus, we examined the perceived quality of chronic care, and its associations with (i) sociodemographic and clinical characteristics, and (ii) diabetes distress. Methods: In total, 216/460 (47%) completed a self-administered survey assessing sociodemographic characteristics, patient assessed chronic illness care (PACIC-20, scale of 1–5) and diabetes distress (PAID-20, scale of 0–100), and 197 had full quality of care data for assessment. We obtained clinical data from national registers and used linear and logistic regression models to examine associations. Results: The mean (SD) PACIC score was 2.6 (0.9) (score range 1–5). Lower PACIC scores were associated with female sex and current unemployment, and with receiving diabetes care in general practice compared with hospital outpatient clinics [mean difference: −0.4 (95% confidence interval (CI) (−0.7 to −0.2)]. People with upper quartile PACIC scores were less likely to report high diabetes distress compared with people with lower quartile PACIC scores [odds Ratio 0.3 95%CI (0.1–0.8)]. Conclusion: Higher quality of care was associated with lower diabetes distress among adults with early onset type 2 diabetes mellitus, but respondents reported less than optimal quality in several core areas of chronic care.